Application of artificial intelligence in modern weapon systems - opportunities and threats in armed conflicts - Zbigniew Małodobry; Karolina Nastaj-Sałek; Katarzyna Cyrkun; Wojciech Jakubiec (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The aim of the work is to analyze the role of artificial intelligence in modern weapon systems, taking into account its potential, threats and ethical challenges. The main objective of the article is to assess the impact of AI on the effectiveness of military operations, security, as well as the potential in the context of weapon autonomy and international regulations. Research problems focus on questions about the impact of AI on decisions made during armed conflicts, threats related to autonomous weapon systems and ethical and legal challenges related to their use. Research hypotheses assume that the implementation of AI can increase the precision and effectiveness of military operations, but at the same time lead to serious challenges in terms of responsibility and the risk of conflict escalation. The research was conducted using the qualitative method, based on the analysis of the literature on the subject and reports on the use of AI in the armies of various countries. The research tool was a review of case studies and analysis of international documents. The conclusions emphasize the need to create international legal regulations regarding the use of AI in weapons to ensure responsible.